Signatures from primordial black hole evaporation. Issue 1 (1st February 2023) - Calabrese, Roberta
Abstract: Primordial Black Holes are hypothetical Black Holes formed in the very early universe and are potential Dark Matter Candidates. We focus on the primordial black hole mass range [5 · 10 14 − 1 · 10 16 ] g. Their evaporation can produce detectable signals in existing experiments. We study neutrinos emitted by PBHs evaporation. The interaction of neutrinos emitted from primordial black hole evaporation can interact through the coherent elastic neutrino-nucleus scattering producing an observable signal in multi-ton DM direct detection experiments. The non-observation of such signals can be used to place forecast constraints on the fraction of Dark Matter composed of Primordial Black Holes. This talk is based on [1]